Curcumin induces apoptosis in JAK2‐mutated cells by the inhibition of JAK2/STAT and mTORC1 pathways. Issue 6 (29th April 2019) - Petiti, Jessica; Rosso, Valentina; Lo Iacono, Marco; Panuzzo, Cristina; Calabrese, Chiara; Signorino, Elisabetta; Pironi, Lucrezia; Cartellà, Antonio; Bracco, Enrico; Pergolizzi, Barbara; Beltramo, Tiziana; Fava, Carmen; et al.
Abstract: Myeloproliferative neoplasms are chronic myeloid cancers divided in Philadelphia positive and negative. The JAK2 V617F is the most common mutation in Philadelphia negative patients and results in a constitutive activation of the JAK/STAT pathway, conferring a proliferative advantage and apoptosis inhibition. Recent studies identified a functional crosstalk between the JAK/STAT and mTOR pathways. The identification of an effective therapy is often difficult, so the availability of new therapeutic approaches might be attractive. Previous studies showed that curcumin, the active principle of the Curcuma longa, can suppress JAK2/STAT pathways in different type of cancer and injuries. In this study, we investigated the anti‐proliferative and pro‐apoptotic effects of curcumin in JAK2 V617F‐ mutated cells. HEL cell line and cells from patients JAK2 V617F mutated have been incubated with increasing concentrations of curcumin for different time. Apoptosis and proliferation were evaluated. Subsequently, JAK2/STAT and AKT/mTOR pathways were investigated at both RNA and protein levels. We found that curcumin induces apoptosis and inhibition of proliferation in HEL cells. Furthermore, we showed that curcumin inhibits JAK2/STAT and mTORC1 pathways in JAK2 V617F‐ mutated cells. This inhibition suggests that curcumin could represent an alternative strategy to be explored for the treatment of patients with myeloproliferative neoplasms.